The reality of professional development Among Hail University faculty members from their point of view - Shajrawi, Sabah Saleh (Journal of Educational and Psychological Sciences, 2021)
The present study aimed at investigate the reality of professional development Among Hail University faculty members from their point of view. In this study, the researcher used the descriptive and analytical method. To achieve the aim of the study, a questionnaire was done by the researcher. It was accredited valid and reliable. It included three areas (teaching, scientific research, community service) and 36 paragraphs. The study was conducted on a random sample of (126) members from the University of Hail in different disciplines. The results of the study indicated that the total score for the reality of professional development got moderate, with mean of (3.56), and the field of teaching values ​​got moderate and the highest arithmetic mean reaching (3.64), followed by the field of scientific research which got moderate with an arithmetic mean (3.53), It is followed by the field of community service, and he got moderate with a mean (3.50). The results of the study also revealed that there are statistically significant differences at the level of significance (α≤0.05). Due to the variable of gender, college, degree, and experience. The study recommended the following: encouraging the exchange of visits and experiences between faculty members, encouraging faculty members to participate in community service programs and to overcome all difficulties and obstacles and holding symposia in teaching, teaching methods and classroom management.